Growth Response of Aromatic Grasses to Soil Salinity Stress - Sulastri, Yustina Sri; Tampubolon, Sanggam Dera Rosa; Manungkalit, Fernando (Agro Bali : Agricultural Journal, 2025)
This research aims to determine the growth response of vetiver, lemongrass and citronella plants in terms most resistant to soil salinity stress levels. The study was carried out at the screen house of the Faculty of Agriculture, Santo Thomas Catholic University, Medan, which is 32 meters above sea level. This research was carried out in January to March 2024. The study used a factorial, Completely Randomized Design, which consisted of two factors. The first factor is the influence of several aromatic grasses (R), which consist of 3 types: lemongrass, citronella, and vetiver. The second factor is the salinity soil stress (S) level, which consists of five levels: without saline, 25% saline soil, 50% saline soil, 75% saline soil saline, and 100% saline soil. Based on these treatment combinations, there were 15 combinations, and each treatment was repeated 3 times so that 45 plants/pots measured 5L. Parameter observations were carried out during harvesting; the parameters observed were shoot fresh weight, shoot dry weight, root fresh weight, root volume, and root cross-section anatomy. The results of the study can be stated that the factor of several aromatic grasses has a significant effect on shoot fresh weight, shoot dry weight, roots fresh weight, and roots volume, where the best aromatic grasses is vetiver even though it was not significantly different from citronella which is resistant to growth at salinity stress levels of 50% to 100%. The salinity level also has a significant effect where salinity starting from 25% causes a decrease in the fresh weight and dry weight of the shoot of the three aromatic grasses.